Perkembangan Infrastruktur Permukiman Baru terhadap Swadaya di Kelurahan Paccinongan, Kecamatan Somba Opu, Kabupaten Gowa - Ummu Kalsum Basman; Wiwik Wahidah Osman; Muhammad Fathien Azmy (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2017)
The growth of new settlements in Paccinongan Village is one of the physical spreads of the city to the outside (urban sprawl). The development of new settlements must consider the surrounding settlements (independent settlements), both the pattern and the development of its infrastructure in terms of road network infrastructure, drainage, clean water, waste water, waste and electricity. The purpose of this study is to identify infrastructure developments in the pattern of new settlements and self-help within a period of 17 years (2000-2017), identify the integration of new settlement infrastructure to self-help and identify the effect of the development of new settlement infrastructure on self-help. The analytical method used in this research is descriptive qualitative analysis, quantitative descriptive, nearest neighbor distance and spatial. The results showed that within a period of 17 years, the new settlement cluster pattern developed significantly in the period 2010-2014 so that new cluster settlements were formed more and more. In addition, the development of new settlement and self-help infrastructure developed significantly. There are 4 (four) infrastructures that show integration between new settlements and self-help, namely road networks, drainage, clean water and electricity. The development of new settlement infrastructure for self-help is influenced by two aspects namely, social and economic aspects.